Eyewitness to power : the essence of leadership : Nixon to Clinton - Gergen, David R. (David Richmond), 1942- (New York : Simon & Schuster, 2000)
White House advisor to four presidents David Gergen chronicles the ups and downs of presidential leadership over the last thirty years of the twentieth century.
Includes bibliographical references and index.
oif 06/03/15
Loan
Keywords: Presidents -- United States -- Case studies; Executive power -- United States -- Case studies